Optical, physical, and chemical properties of springtime aerosol over Barrow Alaska in 2008. (6th March 2014) - Shantz, N. C.; Gultepe, I.; Andrews, E.; Zelenyuk, A.; Earle, M. E.; Macdonald, A. M.; Liu, P. S. K.; Leaitch, W. R.
ABSTRACT Airborne observations from four flights during the 2008 Indirect and Semi‐Direct Aerosol Campaign (ISDAC) are used to examine some cloud‐free optical, physical, and chemical properties of aerosol particles in the springtime Arctic troposphere. The number concentrations of particles larger than 0.12 µm (Na>120), important for light extinction and cloud droplet formation, ranged from 15 to 2260 cm−3, with the higher Na>120 cases dominated by measurements from two flights of long‐range transported biomass burning (BB) aerosols. The two other flights examined here document a relatively clean aerosol and an Arctic Haze aerosol impacted by larger particles largely composed of dust. For observations from the cleaner case and the BB cases, the particle light scattering coefficients at low relative humidity (RH<20%) increased nonlinearly with increasing Na>120, driven mostly by an increase in mean sizes of particles with increasing Na>120 (BB cases). For those three cases, particle light absorption coefficients also increased nonlinearly with increasing Na>120 and linearly with increasing submicron particle volume concentration. In addition to black carbon, brown carbon was estimated to have increased light absorption coefficients by 27% (450 nm wavelength) and 14% (550 nm) in the BB cases. For the case with strong dust influence, the absorption relative to submicron particle volume was small compared with the other cases. There was a slight gradient of Passive Cavity Aerosol Spectrometer Probe (PCASP) mean volume diameter (MVD) towards smaller sizes with increasing height, which suggests more scavenging of the more elevated particles, consistent with a typically longer lifetime of particles higher in the atmosphere. However, in approximately 10% of the cases, the MVD increased (>0.4 µm) with increasing altitude, suggesting transport of larger fine particle mass (possibly coarse particle mass) at high levels over the Arctic. This may be because of transport of larger particles at higher elevations and relatively slow deposition to the surface.